Memory and the history of geographical knowledge: the commemoration of Mungo Park, African explorer - Withers, Charles W.J. (Journal of historical geography, 2004)
Memory is the subject of widespread attention in numerous disciplines. In historical studies in particular, a range of work has explored the role of memory and the processes of memorialisation and of commemoration through which past events had and may continue to have meaning. Relatively little attention has been paid to the place of memory in relation to the history of geographical knowledge. Through an examination of the varied commemoration of the African explorer Mungo Park, and with reference to work in the history of science and in book history, this paper addresses this gap and discusses the implications of work on memory for an understanding of geographical knowledge in historical context.